Common evaluation pitfalls in touch-based authentication systems - Georgiev, M; Lovisotto, G; Eberz, S; Turner, H (University of Oxford, 2021)
This dataset contains the data collected and used in the paper “Common Evaluation Pitfalls in Touch-Based Authentication Systems”.